Evaluation of the early-age-shrinkage of Fiber Reinforced Concrete (FRC) using image analysis methods. (30th December 2015) - Mazzoli, Alida; Monosi, Saveria; Plescia, Eleonora Stella
Highlights: Cracking of concrete due to early-age shrinkage leads to several problems. Fibers in concrete try to reduce the propagation of the early-age-shrinkage cracking. The effectiveness in preventing the growth of the cracks is analyzed using image analysis. The addition of PP and PE macro fibers exhibits the best performance. Abstract: Cracking of concrete due to early-age shrinkage is a common problem that generally leads to several problems experienced by concrete structures, mainly influencing and reducing durability and lifetime. This is of particular relevance in the case of slabs type structures such as pavements, industrial floors, bridge decks, tunnel lining and precast elements, that show much larger surface areas compared with other kinds of structural components, such as beams and columns. In addition, the cracks allow water and other chemical agents to penetrate into concrete and get in touch with steel reinforcements, leading to reinforcement corrosion, even to breakage. Consequently, curing is the unique traditional method to avoid such problems. However, in certain applications, due to the severe environmental conditions and/or due to the actual dimensions of structural elements, curing does not fit the purpose in the prevention of cracks. For the above said, fibers have been incorporated in concrete to reduce and/or prevent the propagation of the early-age-shrinkage cracking. In fact, the utilization of fibers has increased progressively over the past years in structural applications. The present paper focuses on early-age shrinkage cracking with a special attention given to new concretes aiming at reduced shrinkage phenomena through the addition of different types of macro fibers within the cement matrix. In order to estimate the effectiveness in preventing the growth of the cracks, an easy methodology, based on image analysis (IA), has been developed. The results show different considerations regarding distinct materials: in terms of the effectiveness of fibers, the addition of polypropylene and polyethylene macro fibers exhibits the best performance and leads to a certain delay and a wide decreasing in cracking formation. The use of fibers has been found to be very effective in the width reduction of the cracks and, even if not so significantly, in the length reduction.